Discovery of wheat bran extract’s anti-aging potential against D-galactose-induced oxidative stress in a rat aging model - Kobayashi, Kaori (My University, 2025)
Aging is a complex biological process associated with various health complications that require the development of effective interventions for healthy aging. Wheat bran extracts (WBE) have emerged as a promising natural alternative due to their rich composition of bioactive compounds, including phenolic compounds, dietary fiber, and arabinoxylans, which contribute to their functional properties in both food and cosmetic applications. This study also has the potential to contribute to the Sustainable Development Goals (SDGs) by reducing wheat bran as waste, which is discarded in large quantities. The present study explores the antioxidant and enzyme inhibitory activities of WBEs, emphasizing their potential for the new approach of wheat bran extracts as natural preservatives and anti-aging agents. In addition, the study seeks to bridge the gap in understanding the mechanisms by which WBEs exert their beneficial effects. The primary objective of this research is to evaluate the potential of WBEs as functional ingredients for food and cosmetic applications, particularly their antioxidant and enzyme-inhibitory activities. The study aims to determine the effectiveness of WBE supplementation in modulating oxidative stress and aging-related biomarkers in an experimental animal model. Furthermore, research investigates how WBEs impact biological processes such as cellular aging, metabolic regulation, and tissue-specific oxidative responses. A research study was conducted using a D-galactose-induced aging rat model to further evaluate the effects of WBE supplementation on aging-related parameters. Female Wistar rats were divided into four groups: (1) saline-injected negative control, (2) D-galactose-injected positive control, (3) D-galactose-injected with a dietary 5% wheat bran extract (WBE) supplement, and (4) D-galactose-injected with a dietary 10% WBE supplement. During a six-week period, physical parameters, antioxidant enzyme activities, and aging markers were assessed. Measurement of body fat percentages, erythrocyte superoxide dismutase (SOD) activity, and beta-galactosidase activity in liver tissue. Furthermore, Western blot analysis was performed to assess protein quantification and expression of SOD, catalase, and telomerase reverse transcriptase to evaluate systemic oxidative stress markers. Supplementation with WBE was found to have a significant impact on the maintenance of body fat percentages, with a mean value observed in the WBE group being approximately 30 %, compared to an average of 23 % in the control group (P <0.05). The antioxidant enzyme activity exhibited a dose-dependent increase, with the erythrocyte SOD activity reaching 42,368 U/mg in the 10 % WBE group. Beta-galactosidase activity in liver tissue differed significantly among treatment groups, suggesting WBE’s influence on cellular aging. In addition, biochemical assays demonstrated reductions in lipid peroxidation markers, further supporting WBE’s antioxidative potential. Conversely, protein expression levels of SOD, catalase, and telomerase reverse transcriptase remained unaltered, suggesting tissue-specific responses that necessitate further investigation. The findings suggest that WEB supplementation has the capacity to modulate aging-related parameters and oxidative stress markers, particularly in directly exposed tissues such as erythrocytes. The potential applications of WBEs in both food and cosmetics highlight their versatility as functional ingredients. Their antioxidant, antimicrobial, and enzyme-inhibitory properties render them promising candidates for natural preservatives and anti-aging formulations. While preliminary results support their role in anti-aging interventions, further comprehensive in vivo studies are required to elucidate the bioavailability and efficacy of WBE-derived bioactive compounds across various biological systems. Mechanistic studies are also required to facilitate a more complete understanding of the molecular pathways involved in WBE-induced protective effects.
Keywords: Wheat bran extracts; D-galactose aging model; Oxidative stress; Mitochondrial dysfunction; Reactive oxygen species